Experimental ethology of intensively reared lowland pacas (Cuniculus paca) - Hosken, Fábio Morais; de Oliveira, Matheus Henrique Vargas [UNESP]; Malheiros, Jessica Moraes; Martins, Eduardo Henrique [UNESP]; Ferreira, Felipe Norberto Alves; Ferreira, Walter Motta; das Neves Mota, Katiuscia Cristina; Lara, Leonardo Boscoli (Springer Nature, 2021)
The objective of this study was to evaluate and to describe the main behaviors of family groups of lowland pacas (Cuniculus paca) raised in a commercial breeding facility. We used 24 adult pacas, 16 females and 8 males, with a mean live weight of 8.2 kg and age ranging from 2 to 4 years. The animals were kept in groups of two females and one male per enclosure. Cameras were used to monitor the animals. The behaviors identified were divided into five categories (maintenance, exploratory, social interaction, reproductive, and environmental interaction). A completely randomized design in a split-split plot arrangement with three treatment factors was used: sex, period of the day, and season. The frequencies of the maintenance and environmental interaction behavioral categories were significantly higher during the day compared to the nocturnal period (P < 0.05). The duration of each behavioral category differed significantly (P < 0.05) between day and night. The frequencies of the maintenance and reproductive behavioral categories were significantly higher during the dry season compared to the rainy season (P < 0.05) and the relative duration of behaviors of the environmental interaction category was shorter during the dry season (P < 0.05). Females exhibited a significantly higher frequency of maintenance and environmental interaction than males (P < 0.05) and the duration of environmental interaction was shorter (P < 0.05) in females. The present results add to the existing knowledge on the behavior of lowland pacas raised in captivity for production of this wild species which is in the stage of domestication.
Keywords: Animal production; Commercial breeding; Ethogram; Wild animal